Maternal High Fat Diet Alters Gut Microbiota of Offspring and Exacerbates DSS-Induced Colitis in Adulthood - Xie, Runxiang; Sun, Yue; Wu, Jingyi; Huang, Shumin; Jin, Ge; Guo, Zixuan; Zhang, Yujie; Liu, Tianyu; Liu, Xiang; Cao, Xiaocang; Wang, Bangmao; Cao, Hailong (Frontiers in Immunology, 2018)
Abstract Background: Accumulating evidence shows that high fat diet is closely associated with inflammatory bowel disease. However, the effects and underlying mechanisms of maternal high fat diet (MHFD) on the susceptibility of offspring to colitis in adulthood lacks confirmation. Methods: C57BL/6 pregnant mice were given high fat diet (60 E% fat, MHFD group) and control diet (10 E% fat, maternal control diet (MCD) group) during gestation and lactation respectively. After weaning, the intestinal development, mucosal barrier function, microbiota and mucosal inflammation of 3 week-old offspring were assessed. All mice were then fed with control diet until 8 weeks of age and the microbiota were analyzed. Afterwards, offspring were treated with 2% DSS solution for 5 days and the severity of colitis was assessed. Results: The offspring in MHFD group were significantly heavier than those in MCD group only at 2, 3, 4 weeks of age, while no differences were found in the body weight between two groups at other measured time points. Compared with MCD group, MHFD significantly inhibited intestinal development and disrupted barrier function in 3 week-old offspring mice. Although HE staining showed no obvious microscopic inflammation in both groups of 3 week-old offspring mice, increased production of inflammatory cytokines indicated low grade of inflammation was induced in MHFD group. Moreover, analysis of the 3 week-old offspring feces indicated that the microbiota compositions and diversity were significantly changed in MHFD group. Interestingly after 5 weeks consumption of control diet in both groups, the microbiota composition of offspring in MHFD group was still different from that in MCD group, although the bacterial diversity was partly recovered at 8 week of age. Finally, after DSS treatment in adult, MHFD significantly exacerbated the severity of colitis and increased the production of proinflammatory cytokine. Conclusions: Our data reveal that MHFD in early life can inhibit intestinal development, induce dysbiosis and low grade of inflammation and lead to the disruption of intestinal mucosal barrier in offspring mice, and then enhance DSS-induced colitis in adulthood.